2022
DOI: 10.1186/s13287-022-03041-5
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells for treatment of liver fibrosis/cirrhosis: clinical progress and therapeutic potential

Abstract: Cost-effective treatment strategies for liver fibrosis or cirrhosis are limited. Many clinical trials of stem cells for liver disease shown that stem cells might be a potential therapeutic approach. This review will summarize the published clinical trials of stem cells for the treatment of liver fibrosis/cirrhosis and provide the latest overview of various cell sources, cell doses, and delivery methods. We also describe the limitations and strengths of various stem cells in clinical applications. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 148 publications
0
34
0
Order By: Relevance
“…Despite the promising results of therapeutic candidates for ALD in preclinical studies, their efficacy has been less than expected or not observed in clinical trials. The therapeutic effects of stem cells have been proved in chronic liver diseases such as ALD, NAFLD and acute liver failure [176,177]. Pluripotent stem cells, embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) can differentiate into hepatocyte-like cells [178].…”
Section: Stem Cell Therapy For Aldmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the promising results of therapeutic candidates for ALD in preclinical studies, their efficacy has been less than expected or not observed in clinical trials. The therapeutic effects of stem cells have been proved in chronic liver diseases such as ALD, NAFLD and acute liver failure [176,177]. Pluripotent stem cells, embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) can differentiate into hepatocyte-like cells [178].…”
Section: Stem Cell Therapy For Aldmentioning
confidence: 99%
“…Because numerous pre-clinical studies have proved the prospective potential of stem cell therapy, an increasing number of clinical trials are being conducted [177,225]. However, actual clinical application of stem cells for chronic liver disease is still challenging [22,177,225].…”
Section: Limitations Of Stem Cells Including Mscs Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the percentage of stem cells among umbilical cord mononuclear cells decrease as the pregnancy progresses, from 11% at week 17 to 1% at week 38; however, these cells have a distinct advantage over bone marrow HSCs because they graft 10 to 50 times better on hosts xenogenesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell transplantation has emerged as the most promising treatment for liver fibrosis since the advent of regenerative medicine (7)(8)(9). Stem cells are a population of cells with self-renewal, proliferation, and pluripotent differentiation potential that can differentiate into multiple cell types under defined conditions (10,11).…”
mentioning
confidence: 99%